Wnt/frizzled signaling requires dPRR, the drosophila homolog of the prorenin receptor - Büchling, Tina; Bartscherer, Kerstin; Ohkawara, Bisei; Chaudhary, Varun; Spirohn, Kerstin; Niehrs, Christof; Boutros, Michael (Current biology, 2010)
Wnt/Wg signaling pathways are of key importance during development and disease [1, 2, 3, 4]. Canonical and noncanonical Wnt/Frizzled (Fz) pathways share a limited number of signaling components that are part of the membrane proximal signaling complex. In Drosophila, Fz [5, 6, 7] and Dishevelled (Dsh) [8, 9] are the only two components known to be involved in both Wnt/β-catenin and planar cell polarity (PCP) signaling. PCP signaling is required for the planar polarization of epithelial cells [10, 11], which occurs, for instance, during hair orientation and gastrulation in vertebrates [12]. Both pathways have been studied intensively in the past years. However, it still remains unresolved whether additional components are required at the receptor complex. Here we identify the Drosophila homolog of the mammalian prorenin receptor (dPRR) as a conserved modulator of canonical Wnt/β-cat and Fz/PCP signaling. We show that dPRR depletion affects Wg target genes in cultured cells and in vivo. PRR is required for epithelial planar polarity in Drosophila and for convergent extension movements in Xenopus gastrulae. Furthermore, dPRR binds to Fz and Fz2 receptors. In summary, our data suggest that dPRR has an evolutionarily conserved role at the receptor level for activation of canonical and noncanonical Wnt/Fz signaling pathways.
Gesehen am 16.03.2023